Taking history on tour: lowering the disciplinary drawbridge. Issue 2 (2nd September 2017) - Harris, Karen L.
ABSTRACT: This article considers the relationship – or lack thereof – between history and tourism. It examines the emerging dual-domain of these two 'disciplines' both in terms of the objections that divide them and the attributes that bind them. It touches on the history of these two diverse fields in terms of their respective educational and academic positions, the one a product of the classical era and the other emerging in modern times. It contemplates public history, as well as the various skills inherent to history that are of relevance to tourism, as possible conduits to converge this divergence in a specifically South African context.